(untitled) (Research, Society and Development, 2022)
Leprosy is a chronic, granulomatous, slowly evolving disease caused by Mycobacterium leprae, which affects the skin and peripheral nervous system, generating physical disabilities. Despite the use of multidrug therapy, the number of new cases remains constant in many countries. The possibility of global elimination of leprosy has been discussed by the WHO and by several authors, thus, the present study aims to present the challenges to be overcome in relation to its diagnosis and treatment so that this goal is achieved. For this, file searches were carried out in the SCOPUS, PUBMED, SCIELO, Google Scholar databases. Since the diagnosis of leprosy is based on a few clinical signs, many professionals have difficulty recognizing findings suggestive of the disease. One of the problems to be overcome is the absence of an exam that presents high specificity and sensitivity for all clinical forms. The development of a fast, sensitive, and non-invasive method is of great importance for the definitive diagnosis. Early diagnosis is a crucial factor for disease control and can prevent the onset of disabilities. The treatment of leprosy, its adherence and its conclusion are essential, however, the number of people who adhere to the medication has been inconsistent. In addition, the resistance of M. leprae to currently available drugs also prove to be an obstacle to be overcome. Thus, there are many obstacles that remain to be overcome so that leprosy can be eradicated in the world.